The Great Escape: A Phenomenological and Structural Equation Analysis of #KaburAjaDulu and Transnational Migration Aspirations among Indonesia’s Urban Gen Z - Iis Sugandhi; Susi Diana; Yuniarti Maretha Pasaribu (HM Publisher, 2025)
In the wake of post-pandemic shifts in labor dynamics, the hashtag #KaburAjaDulu has emerged as a potent cultural signifier among Indonesian youth, reflecting a deepening disillusionment with the neoliberal promise of upward mobility. This study investigates the intersection between quiet quitting—defined as psychological disengagement from labor—and migration aspirations, or physical withdrawal, as a singular phenomenon of existential resistance. The novelty of this research lies in its synthesis of digital anthropology and organizational sociology to treat workplace disengagement and migration as two points on the same continuum of escape. Adopting a mixed-methods approach, the study utilized Interpretative Phenomenological Analysis (IPA) through semi-structured interviews with 30 young professionals in Jakarta’s creative and corporate sectors. These qualitative findings were triangulated with a quantitative validation through Structural Equation Modeling (SEM) of 1,000 digital entries to ensure the interview themes were representative of the broader digital discourse. Findings reveal three master themes: The Working Dead Syndrome, depicting emotional detachment; Digital Solidarity, where the hashtag serves as a third space for collective survival; and The Green Pasture Mirage, where migration represents a quest for systemic dignity. SEM analysis confirms that Workplace Toxicity and Digital Peer Support significantly predict Migration Aspirations, with fit indices meeting rigorous publication standards. The study concludes that to retain Gen Z talent, the Indonesian corporate sector must move beyond superficial perks toward genuine structural reform.